U źródeł żądzy pisania Czesława Miłosza - Szawerna-Dyrszka, Anna (Śląskie Studia Polonistyczne, 2013)
The article show what turned out decisive in Miłosz’s childhood and early youth times that made him later on decide to become a writer. The author examines circumstances under which Miłosz’s linguistic sensitivity in the “pre-writing” period, looks at his first individual reading, and writing samples subsequently. The correspondence between a beginner writer with Jarosław Iwaszkiewicz proves a hypothesis that Miłosz’s writing desire is secondary from the beginning in the light of his reality desire. A written word is aimed at capturing it and maintaining it most directly and as it is possible, namely referring directly to the world (not the written word). The aim of writing, on the other hand, derives from curiosity of the thing, the same that accompanied Miłosz before he had learned how to read and write.